Conceptual role semantics and the reference of moral concepts - Sinclair, Neil (Wiley, 2017)
This paper examines the prospects for a conceptual or functional role theory of moral concepts. It is argued that such an account is well-placed to explain both the irreducibility and practicality of moral concepts. Several versions of conceptual role semantics for moral concepts are distinguished, depending on whether the concept-constitutive conceptual roles are wide or narrow normative or non-normative and purely doxastic or conative. It is argued that the most plausible version of conceptual role semantics for moral concepts involves only ‘narrow’ conceptual roles, where these include connections to motivational, desire-like, states. In the penultimate section it is argued, contrary to what Wedgwood, Enoch and others have claimed, that such an account of moral concepts cannot plausibly be combined with the claim that moral concepts refer to robust properties.